Electrophotographic member, electrophotographic image formation device, and conductive resin composition

By combining FSI Anion without C-F bonds with aromatic ring and double bond polyester resin, the problem of lower conductivity of electronic photo members in high voltage environments is solved, and a stable formation of high-quality images and environmentally friendly conductive layer is achieved.

JP2025015441APending Publication Date: 2025-01-30CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024101245
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-06-24
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing electronic photo members tend to reduce their conductivity in high-voltage environments for a long time, affecting image quality stability, and traditional PFAS compounds containing C-F bonds are limited due to environmental residues and bioaccumulation.

Method used

FSI Anion without C-F bonds is used to combine with polyester resin containing aromatic rings and double bonds to form electronic photo members with high conductivity and stability. Polyester resins such as polyethylene terephthalate and modified polyethylene terephthalate are used to form a stable ionic conductive layer with imidazolium or pyridinium ions with FSI Anion and double bond structure.

Benefits of technology

Maintaining electrical conductivity in long-term use in high-voltage environments ensures the formation of high-quality electronic photo images and reduces the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015441000001_ABST
    Figure 2025015441000001_ABST
Patent Text Reader

Abstract

To provide electrophotographic members of which electric conductivity is hard to fall even with a use over a long period of time under an environment in which a high voltage is applied.SOLUTION: An electrophotographic member has a conductive resin layer, and the resin layer includes: aromatic ring-containing polyester; and a cation that has a fluorosulfonyl imide anion and a double bond. The aromatic ring-containing polyester is polyester that is selected from a group consisting of (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) modified polyethylene terephthalate in which a ratio of an acid monomer unit other than a terephthalic acid unit is equal to or less than 6 mol% in a total monomer unit, and (iv) modified polyethylene naphthalate in which a ratio of the acid monomer unit other than a naphthoic acid unit is equal to or less than 6 mol% in the total monomer unit, or a mixture that consists of two or more polyesters selected from the (i) to (iv).SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrophotographic members, electrophotographic imaging devices, and conductive resin compositions. [Background technology]

[0002] Patent Document 1 discloses a conductive belt for electrophotography that uses an ionic conductive agent containing a perfluoroalkylsulfonylimide anion as the negative ion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-132329 A [Patent Document 2] JP 2020-024404 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, restrictions on the use of perfluoroalkyl and polyfluoroalkyl substances (hereinafter also referred to as "PFAS"), which are considered to have high environmental persistence and bioaccumulation, are being considered. Therefore, the present inventors have studied an ionic conductive agent containing a bis(fluorosulfonyl)imide anion (hereinafter also referred to as "FSI anion"), which does not have a C-F bond in the molecule and does not belong to PFAS. Here, the use of FSI anion in electrophotographic members is disclosed in Patent Document 2. Specifically, Example 6 of Patent Document 2 describes a development blade using an FSI anion and a cation containing a long-chain alkyl chain. According to the study by the present inventors, it is possible to obtain an ionic conductive agent containing an FSI anion (hereinafter, "FSI ion The electrophotographic member having a resin layer made conductive by using a conductive agent (also called a "conductive agent") is, for example, Compared with the case where an ionic conductive agent containing fluoromethanesulfonylimide (TFSI) anion was used, the conductivity was more likely to decrease during long-term use.

[0005] At least one aspect of the present disclosure is directed to providing an electrophotographic member whose electrical conductivity is unlikely to decrease even after long-term use in an environment where a high voltage is applied. At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images even after long-term use. Furthermore, at least one aspect of the present disclosure is directed to providing a conductive resin composition whose electrical conductivity is unlikely to decrease even after long-term current flow. [Means for solving the problem]

[0006] In accordance with at least one aspect of the present disclosure, there is provided an electrophotographic member comprising: The electrophotographic member has a resin layer, The resin layer has electrical conductivity, The resin layer is An aromatic ring-containing polyester; a fluorosulfonylimide anion and a cation having a double bond; Including, The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) Modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units is 6 mol % or less of the total acid monomer units, and (iv) Modified polyethylene naphthalate in which the proportion of acid monomer units other than naphthalene acid units is 6 mol % or less of the total acid monomer units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv) above. An electrophotographic member is provided.

[0007] According to at least one aspect of the present disclosure, there is also provided an electrophotographic image forming apparatus including the above-described electrophotographic member as an intermediate transfer belt.

[0008] According to at least one embodiment of the present disclosure, there is provided a composition comprising an aromatic ring-containing polyester, a fluorosulfonylimide anion, and a cation having a double bond, The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) Modified polyethylene terephthalate in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units, and (iv) Modified polyethylene naphthalate in which the proportion of acid units other than naphthalene acid units is 6 mol % or less of the total acid units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv) above. Effect of the Invention

[0009] According to at least one aspect of the present disclosure, there is provided an electrophotographic member whose conductivity is unlikely to decrease even after long-term use in an environment where a high voltage is applied. Also, according to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images even after long-term use. Furthermore, according to at least one aspect of the present disclosure, there is provided a conductive resin composition whose conductivity is unlikely to decrease even after long-term current application. [Brief description of the drawings]

[0010] [Figure 1] An explanatory diagram of ion dissociation in a resin layer according to one embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view showing an example of an electrophotographic image forming apparatus; [Diagram 3] FIG. 1 is an explanatory diagram of a configuration of an electrophotographic belt according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, the unit of surface resistivity "Ω / □" means "Ω / square". In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0012] As mentioned above, the ionic conductive agent containing the FSI anion (hereinafter referred to as the "FSI ionic conductive agent") The electrophotographic member having a resin layer made conductive by using, for example, trifluoromethan In some cases, the conductivity was more likely to decrease over time than when an ionic conductive agent containing a tetrafluoroethylene sulfonyl imide (TFSI) anion was used. The reason why the conductivity of the conductive resin layer tends to decrease when using an FSI ionic conductive agent is presumed to be due to the fact that the FSI anion does not have a perfluoroalkyl group and therefore has a small molecular size.

[0013] Patent Document 2 discloses that the movement of ions can be suppressed by entanglement of the molecular chains of ions and matrix resin. Based on the invention described in Patent Document 2, the present inventors have investigated the combination of FSI anion with an imidazolium cation to which a long-chain alkyl group of C9 to C20 is bonded, hoping to suppress the movement of FSI. However, even with this combination, the effect of preventing the decrease in conductivity over time was extremely limited in electrophotographic members to which a high voltage is applied, such as an intermediate transfer belt.

[0014] In electrophotographic materials to which high voltage is applied, it is presumed that even if the FSI anion is combined with an imidazolium cation to which a long-chain alkyl group of C9 to C20 is bonded, the movement of the FSI anion with a small molecular size cannot be sufficiently prevented. Therefore, the imidazolium cation moves to the negative electrode side, and the FSI anion moves to the positive electrode side, and the imidazolium cation and FSI anion that reach the electrode are reduced and oxidized, respectively, to lose their charge. The conductivity of an ionic conductive agent is proportional to the number of carrier ions that are the carriers of conductivity. In other words, since electrical resistivity is the reciprocal of electrical conductivity, some carrier ions lose their charge due to the application of a voltage for a long time. As a result, the number of carrier ions decreases, and it is considered that the electrical resistivity increases.

[0015] Therefore, the present inventors conducted research to obtain a conductive resin layer that can prevent the conductivity from changing over time even when a voltage is applied, assuming the use of an FSI anion, and found that a resin layer containing an FSI anion, an aromatic-containing polyester, and a cation having a double bond is effective in achieving the above object.

[0016] The present inventors speculate as follows as to why the resin layer can suppress the change in electrical conductivity over time even when a high voltage is applied. In general, in a resin layer in which electrical conductivity is imparted by an ionic conductive agent, it is considered that an equilibrium state exists between a salt state of cations 101 and anions 102 and a state in which cations 101 and anions 102 are dissociated to form carrier ions (103) as shown in Fig. 1A. In other words, a portion of the ionic conductive agent is not dissociated and does not contribute to electrical conductivity.

[0017] On the other hand, in the resin layer according to the present disclosure, as shown in Fig. 1B, the cation-anion (102) bond is weakened by the π-π interaction (105) between the π electrons of the aromatic ring (104) of the aromatic ring-containing polyester and the π electrons of the cation (101) having a double bond, resulting in a state in which ionic dissociation is easily caused. In other words, the equilibrium state is shifted in the direction of increasing the number of carrier ions. In addition, as described above, even if the carrier ions, cations and anions, move in the resin layer, lose charge, and the number of carrier ions decreases, causing the equilibrium state to be broken, ion dissociation quickly occurs to maintain the equilibrium state. Therefore, the number of carrier ions is unlikely to change even if a voltage is continuously applied. As a result, it is believed that the resin layer has a reduced change in conductivity even after long-term use.

[0018] Hereinafter, embodiments of the electrophotographic member according to the present disclosure will be described in detail, however, the present disclosure is not limited to the following embodiments.

[0019] <Electrophotographic materials> The electrophotographic member according to one embodiment of the present disclosure has a resin layer having an aromatic ring-containing polyester, a fluorosulfonylimide anion, and a cation having a double bond. The resin layer has electrical conductivity. The resin layer may contain additives other than the above to the extent that the effect of the present disclosure is not impaired.

[0020] The shape of the electrophotographic member is not particularly limited. That is, the electrophotographic member according to one embodiment of the present disclosure can be, for example, a belt having an endless shape (hereinafter, also referred to as "electrophotographic belt") or an electrophotographic roller having a roller shape. The electrophotographic member is preferably an electrophotographic belt, and more preferably an intermediate transfer belt.

[0021] FIG. 3A shows a perspective view of a conductive belt 300 as an example of an electrophotographic member according to one embodiment of the present disclosure. As an example of the layer structure, a single-layer structure in which the cross section of the line AA' in Fig. 3A is composed of only a resin layer 301 as shown in Fig. 3B can be given. In this case, an outer surface 301-1 of the resin layer becomes, for example, a bearing surface of unfixed toner when the conductive belt is used as an intermediate transfer belt, that is, the outer surface of the conductive belt.

[0022] As another example, the cross section along line AA' has a laminated structure including base layer 303 and resin layer 301 covering the outer peripheral surface of the base layer, as shown in Fig. 3C. In this structure, outer surface 301-1 of resin layer 301 on the side opposite to the side facing base layer 303 constitutes the outer surface of the conductive belt.

[0023] As yet another example, the cross section taken along line AA' has a laminated structure including a resin layer 301 and a surface layer 305 that covers the outer peripheral surface of the resin layer, as shown in Fig. 3D. In this structure, an outer surface 305-1 of the surface layer 305 opposite to the side facing the resin layer 301 constitutes the outer surface of the conductive belt. Still another example is a configuration having a back layer (not shown) that covers the inner circumferential surface of the conductive belt having the configuration shown in FIG. 3B, 3C, or 3D.

[0024] <Resin layer> The thickness of the resin layer is not particularly limited, but when used as an intermediate transfer belt, it is preferably from 10 μm to 700 μm, more preferably from 50 μm to 120 μm. By setting the thickness of the resin layer within the above range, the resin layer can more reliably have the strength, flexibility, bending resistance, etc. required as a member.

[0025] The resin layer can be a layer (surface layer) constituting the outer surface of the electrophotographic member. Specifically, for example, when the electrophotographic member is an intermediate transfer member, the resin layer can be a layer constituting the outer surface of the intermediate transfer belt, which is the toner image bearing surface of the intermediate transfer belt. In addition, the surface of the resin layer may be subjected to surface treatment such as coating of a treatment agent or polishing treatment, or a surface layer for protecting the surface of the resin layer may be provided separately.

[0026] Each material used in the resin layer will be described in detail below. <Polyester containing aromatic ring> The resin layer contains an aromatic ring-containing polyester, which is preferably a matrix resin. Since the aromatic ring ratio in the molecule is high and the effect of promoting ionic dissociation is more easily achieved, the aromatic ring-containing polyester is a polyester selected from the group consisting of (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) modified polyethylene terephthalate in which the ratio of acid units other than terephthalic acid units is 6 mol % or less (e.g., 0 to 6 mol %) of the total acid units, and (iv) modified polyethylene naphthalate in which the ratio of acid units other than naphthalene acid units is 6 mol % or less (e.g., 0 to 6 mol %) of the total acid units, or a mixture of two or more polyesters selected from the group consisting of the above (i) to (iv).

[0027] The aromatic ring-containing polyester more preferably contains at least one selected from the group consisting of polyethylene naphthalate, polyethylene terephthalate, and modified polyethylene terephthalate. The modified polyethylene terephthalate is preferably isophthalic acid-modified polyethylene terephthalate or naphthalene acid-modified polyethylene terephthalate, and particularly preferably isophthalic acid-modified polyethylene terephthalate. It is more preferable that the aromatic ring-containing polyester contains at least one selected from the group consisting of polyethylene naphthalate, polyethylene terephthalate, and isophthalic acid-modified polyethylene terephthalate.It is more preferable that the aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, or (iii) a modified polyethylene terephthalate in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units, and the acid units other than terephthalic acid units are isophthalic acid units. Furthermore, the aromatic ring-containing polyester is more preferably at least one selected from the group consisting of polyethylene naphthalate and polyethylene terephthalate, since this can increase the crystallinity and further improve the strength of the resin layer. It is particularly preferable that the aromatic ring-containing polyester is polyethylene naphthalate or polyethylene terephthalate.

[0028] In this disclosure, the term "monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, in a polyester, an ester bond is considered to be one unit. In mole percent calculations, one unit corresponds to one molecule.

[0029] The aromatic ring-containing polyester may be used alone or in combination of two or more kinds, and may be a blend or an alloy. In addition, other resins may be added to the extent that the effect of the present disclosure is not impaired. As the other resins, known resins may be used. For example, polyether ester amide and the like may be mentioned.

[0030] A specific example of polyethylene naphthalate is "TN-8065S" (product name; manufactured by Teijin Limited). A specific example of polyethylene terephthalate is An example of the isophthalic acid modified polyethylene terephthalate is "TR-8550FF" (trade name; manufactured by Teijin Limited). Also, an example of the isophthalic acid modified polyethylene terephthalate is "IP121B" (trade name; manufactured by Bell Polyester Products Co., Ltd., a polycondensate of terephthalic acid, isophthalic acid and ethylene glycol).

[0031] From the viewpoint of maintaining the strength of the electrophotographic member, the content of the aromatic ring-containing polyester in the resin layer is preferably 50.0 to 99.0 mass %, more preferably 60.0 to 98.0 mass %, even more preferably 70.0 to 98.0 mass %, and even more preferably 75.0 to 98.0 mass %, based on the mass of the resin layer.

[0032] <Bis(fluorosulfonylimide) anion> The resin layer etc. contains a bis(fluorosulfonyl)imide (FSI) anion as an anion. The bis(fluorosulfonyl)imide anion has a structure represented by the following structural formula (1). [ka]

[0033] The resin layer may contain anions other than the FSI anion as necessary, as long as the effects of the present disclosure are not impaired. However, it is preferable that the resin layer contains the FSI anion as the only anion, since this can reduce the environmental dependency of the electrical conductivity of the resin layer. Here, as the other anion that can be used, it is preferable to use an anion that does not have a C—F bond in the molecule and does not belong to PFAS. Examples of anions that do not belong to PFAS include, for example, Cl - , Br - , I - , AlCl4 - , N(CN)2 - Examples of the anions include those represented by the following structural formulas (2) to (4). [ka]

[0034] In structural formulas (2) to (4), R 21 , R 31 , R 41 and R 42 each independently represents any one selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 18 carbon atoms, and an alkoxy group having 1 to 18 carbon atoms. Examples of the hydrocarbon group include a linear or branched saturated hydrocarbon group, a linear or branched unsaturated hydrocarbon group, a substituted or unsubstituted saturated alicyclic hydrocarbon group, a substituted or unsubstituted unsaturated alicyclic hydrocarbon group, and a substituted or unsubstituted aromatic hydrocarbon group.

[0035] R 21Preferred examples of include a hydrogen atom, a linear or branched alkyl group having 1 to 6 carbon atoms (more preferably 1 to 3 carbon atoms), and a substituted or unsubstituted aryl group, specifically, for example, an unsubstituted phenyl group, and a phenyl group substituted with an alkyl group having 1 to 3 carbon atoms (more preferably 1 or 2 carbon atoms). R 31 Preferred examples of the alkyl group include alkyl groups having 3 to 15 carbon atoms (more preferably 6 to 12 carbon atoms). R 41 , and R 42 Preferred examples of the groups are each independently a straight-chain or branched-chain alkyl group having 3 to 15 carbon atoms (more preferably 6 to 12 carbon atoms).

[0036] The anion represented by the above structural formula (2) may be at least one selected from the group consisting of the following anions. Sulfonate ion, methanesulfonate ion, ethanesulfonate ion, 1-butanesulfonate ion, p-toluenesulfonate ion (tosylate ion), 1-octanesulfonate ion, 1-decanesulfonate ion, 1-tetradecanesulfonate ion, 1- The cation is preferably at least one selected from the group consisting of an octadecanesulfonate ion, a hydrogen sulfate ion, a methyl sulfate ion, an ethyl sulfate ion, a 1-butyl sulfate ion, a 1-octyl sulfate ion, a 1-decyl sulfate ion, a 1-tetradecyl sulfate ion, and a 1-octadecyl sulfate ion. More preferably, the cation is at least one selected from the group consisting of a methanoate ion, an ethanoate ion, a p-toluenesulfonate ion, and a hydrogen sulfate ion.

[0037] The anion represented by the above structural formula (3) may be at least one selected from the group consisting of the following anions: Methanoate ion, ethanoate ion, butanoate ion, hexanoate ion, benzoate ion, octanoate ion, decanoate ion, dodecanoate ion, tetradecanoate ion, hexadecanoate ion, octadecanoate ion, methyl carbonate ion, ethyl carbonate ion, butyl carbonate ion, hexyl carbonate ion, octyl carbonate ion, decyl carbonate ion, tetradecyl carbonate ion, and octadecyl carbonate ion. Decanoate ion is more preferred.

[0038] The anion represented by the above structural formula (4) may be at least one selected from the group consisting of the following anions: Phosphinate ion, dimethylphosphinate ion, ethylmethylphosphinate ion, diethylphosphinate ion, dibutylphosphinate ion, bis(2,4,4-trimethylpentyl)phosphinate ion, dioctylphosphinate ion, ditetradecyl phosphinate ion, dioctadecylphosphinate ion, dimethyl phosphate ion, diethyl phosphate ion, dibutyl phosphate ion. More preferably, it is selected from the group consisting of diethylphosphinate ion and bis(2,4,4-trimethylpentyl)phosphinate ion. At least one of the above is preferably bis(2,4,4-trimethylpentyl) It is a phosphinate ion.

[0039] However, it is preferable that the resin layer contains FSI as the only anion, since this can reduce the environmental dependency of the electrical conductivity of the resin layer.

[0040] <Cation having a double bond> The cation having a double bond is not particularly limited as long as it has a double bond in the molecule. It is preferable that the cation is not subject to PFAS. That is, it is preferable that the cation does not have a C-F bond in the molecule.

[0041] The cation having a double bond is preferably, for example, a cation having an aromatic heterocyclic structure, particularly preferably a cation having a nitrogen-containing heteroaromatic ring.Examples of the cation having a nitrogen-containing heteroaromatic ring include, for example, a cation having an imidazolium structure and a cation having a pyridinium structure.That is, the cation having a double bond is preferably at least one cation selected from the group consisting of a cation having an imidazolium structure and a cation having a pyridinium structure.

[0042] In particular, it is more preferable that the cation having a double bond is at least one cation selected from the group consisting of an imidazolium cation having an imidazolium structure represented by the following formula (2-1) and a pyridinium cation having a pyridinium structure represented by the following formula (2-2). [ka]

[0043] In formula (2-1), R1 and R2 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. From the viewpoint of more efficiently generating an interaction between the imidazolium cation and the aromatic ring-containing polyester, when one selected from the group consisting of R1 and R2 is a hydrocarbon group having 5 to 8 carbon atoms (e.g., 8), the other is preferably a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, more preferably a hydrocarbon group having 1 or 2 carbon atoms, and even more preferably a hydrocarbon group having 1 carbon atom. More preferably, R1 and R2 each independently represent a hydrocarbon group having 1 to 4 carbon atoms. [ka]

[0044] In formula (2-2), R3 and R4 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. From the viewpoint of more efficiently generating an interaction between the pyridinium cation and the double bond-containing polyester, when one selected from the group consisting of R3 and R4 is a hydrocarbon group having 5 to 8 carbon atoms (e.g., 8), the other is preferably a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, more preferably a hydrocarbon group having 1 or 2 carbon atoms, and even more preferably a hydrocarbon group having 1 carbon atom. More preferably, R3 and R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms.

[0045] Examples of the hydrocarbon group include, for example, a linear or branched saturated hydrocarbon group, a linear or branched unsaturated hydrocarbon group, a substituted or unsubstituted saturated alicyclic hydrocarbon group, a substituted or unsubstituted unsaturated alicyclic hydrocarbon group, a substituted or unsubstituted aromatic hydrocarbon group, etc. The hydrocarbon group is preferably an alkyl group.

[0046] Specific examples of the imidazolium cation represented by the above formula (2-1) are given below. 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation.

[0047] Specific examples of the pyridinium cation represented by the above structural formula (2-2) are given below. 1-ethylpyridinium ion, 1-butylpyridinium ion, 1-hexylpyridinium ion, 1-octylpyridinium ion, 1-(tert-butyl)pyridinium ion, 1-octyl-4-methylpyridinium ion, and 1-octyl-4-butylpyridinium ion.

[0048] Examples of the cation having a double bond and no aromatic heterocyclic structure include a compound in which a group having a vinyl group is bonded to at least one atom selected from the group consisting of carbon atoms and nitrogen atoms constituting a pyrrolidine ring or a piperidine ring. The above cations may be used alone or in combination of two or more kinds. The resin layer, etc. may contain a cation that does not have a double bond in the molecule as necessary, within a range that does not impair the effects of the present disclosure. The ionic conductive agent is composed of a combination of a fluorosulfonylimide anion and one or more of these cations. For example, the resin layer, etc. contains an ionic conductive agent composed of the above anion and cation.

[0049] In addition, the content of the ionic conductive agent in the resin layer, etc. (the sum of the contents of fluorosulfonylimide anions and cations having a double bond) is preferably 0.1 mass % or more based on the mass of the resin layer. This is because it is easier to impart a predetermined electrical conductivity to the resin layer. There is no particular upper limit to the content, but it is, for example, 15.0 mass % or less. Even if the ionic conductive agent is contained in the resin layer, etc., at a content exceeding 15.0 mass %, the effect of improving electrical conductivity is limited. This is because. The content of the ion conductive agent in the resin layer is preferably in the range of 0.1% by mass to 15.0% by mass. The content may be appropriately selected within this range depending on the electrical conductivity that the resin layer should have. As an example, the content of the ion conductive agent is more preferably 0.5 to 10.0% by mass, and further preferably 2.0 to 7.0% by mass.

[0050] The presence of the ionic conductive agent in the resin layer can be determined by extracting and identifying the ionic conductive agent from the resin layer or the like. A solvent capable of dissolving the ionic conductive agent is selected as the solvent used for extraction. A specific example is methanol. Then, the extract is centrifuged as necessary, and the ionic conductive agent is isolated by liquid chromatography or the like as necessary, and the structures of the cations and anions can be identified by mass spectrometry or NMR measurement. The sum of the contents of the anions and cations in the resin layer can be determined by measuring the mass of the dried product after removing the solvent from the extract. An example of a method for identifying the structures of the cations and anions and measuring the mass is shown below.

[0051] A 200 mg sample is cut out from the resin layer and immersed in 1 mL of methanol, after which 40 kHz ultrasound is applied for 10 minutes to obtain an anion and cation extract. The sample is then centrifuged at 12,000 rpm for 10 minutes using a high-speed centrifuge to separate the supernatant and obtain a solution of the cations and anions. The resulting solution is then subjected to mass spectrometry using a liquid chromatography mass spectrometer. [Mass spectrometry conditions] ·Direct introduction method ·Injection volume: 2μL Ionization method: Electrospray (ESI) ionization

[0052] In addition, after removing methanol from the extract of the cations and anions obtained by the above operation, the extract is redissolved in deuterated methanol to prepare a deuterated methanol solution of the anions and cations. The deuterated methanol solution is 1 Measured by H-NMR. [Measurement conditions] Frequency: 400MHz Number of times: 32 ·Measurement temperature: 25℃

[0053] The above mass spectrometry and 1 The structures of the cations and anions can be identified from the H-NMR spectrum. Furthermore, if the solution does not contain any methanol-soluble components other than the ion conductive agent, the total amount of anions and cations contained in 200 mg of the sample can be determined by measuring the mass of the dried product obtained by removing the methanol from the solution.

[0054] (Additives) The resin layer etc. may contain other components (additives) to the extent that the effects of the present disclosure are not impaired. Examples of the additives include surfactants, antioxidants (e.g., hindered phenol-based, phosphorus-based, sulfur-based, etc.), ultraviolet absorbers, organic pigments, inorganic pigments, pH adjusters, crosslinking agents, compatibilizers, release agents, coupling agents, lubricants, conductive fillers (e.g., carbon black, carbon fiber, carbon nanotubes, conductive tin oxide, conductive mica), polymeric antistatic agents (e.g., polyether amide, polyether ester amide), and the like.

[0055] In addition, adding hydrophilic metal oxide particles (silica, titanium oxide, etc.) forms a conductive path for ion migration, making it possible to further reduce resistance. Therefore, the resin layer, etc., is hydrophilic. Metal oxide particles (silica, titanium oxide, etc.) may be contained. These additives may be used alone or in combination of two or more. The amount of the additives used may be appropriately set and is not particularly limited. The content of the hydrophilic metal oxide particles is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 3.0% by mass, based on the mass of the resin layer, etc. The resin layer etc. may contain a polymeric antistatic agent (e.g., polyetheramide, polyetheresteramide). The content of the polymeric antistatic agent is preferably 1.0 to 30.0% by mass, more preferably 5.0 to 20.0% by mass, based on the mass of the resin layer etc.

[0056] <Surface layer> An example of the surface layer is a layer having excellent abrasion resistance, which contains a cured product of an active energy ray curable resin. Such a second layer can be provided, for example, by applying a composition containing an active energy ray curable resin, such as a photocurable resin, onto the outer peripheral surface of the base layer and curing the composition. The thickness of the surface layer is not particularly limited, but is preferably, for example, 1 to 5 μm.

[0057] <Back layer> Examples of the back layer include a resin layer for reinforcing the base layer and a conductive layer for making the inner peripheral surface of the electrophotographic belt conductive. The thickness of the back layer is not particularly limited, but is preferably, for example, 0.05 to 10 μm.

[0058] In the following, an electrophotographic belt will be described as an example. The use of the electrophotographic belt in an electrophotographic image forming apparatus is not particularly limited, but for example, an intermediate transfer belt carrying an unfixed toner image on its outer surface is preferably used as a transfer conveyor belt carrying a recording material on its outer surface. The electrophotographic member according to one embodiment of the present disclosure can be particularly preferably used as an intermediate transfer belt.

[0059] In addition, when the electrophotographic member is used as an intermediate transfer belt, the surface resistivity ρs measured on the outer surface of the resin layer at a temperature of 23° C. and a relative humidity of 50% is 1.0×10 6 ~9.9×10 12 Ω / □ is preferable, and 1.0×10 6 ~1.0×10 12 Ω / □ is more preferable, and 1.0×10 6 ~9.9×10 10 It is more preferably Ω / □.

[0060] Surface resistivity is 1.0 x 10 6 If the surface resistivity is 9.9×10 Ω / □ or more, the transfer electric field during the secondary transfer can be obtained more easily, and the occurrence of voids and roughness in the electrophotographic image can be easily prevented. 12 By setting the resistivity at Ω / □ or less, it is not necessary to excessively increase the transfer voltage during secondary transfer, and it is possible to further suppress the increase in size of the power supply and the increase in cost. Note that, depending on the conditions during secondary transfer, transfer may be possible even if the surface resistivity is outside the above range, so the surface resistivity of the electrophotographic member is not necessarily limited to the above range.

[0061] <Method of Manufacturing Electrophotographic Member> The resin layer can be formed using a conductive resin composition (e.g., a resin composition obtained by melt-kneading various components) containing the above-mentioned aromatic ring-containing polyester, a fluorosulfonylimide anion and a cation having a double bond (FSI ion conductive agent), and other additives as necessary.

[0062] For example, the electrophotographic member having the resin layer can be formed by the following method: The resin composition is pelletized, and the pellets are molded by a known molding method such as continuous melt extrusion, injection molding, stretch blow molding, or inflation molding. For example, a seamless belt can be formed into an electrophotographic member. The electrophotographic member is preferably an electrophotographic belt having an endless belt shape. As described above, the electrophotographic member may be subjected to a surface treatment such as coating with a treatment agent or polishing.

[0063] <Electrophotographic image forming apparatus> Using FIG. 2, an electrophotographic image forming apparatus (electrophotographic apparatus) having an intermediate transfer member (hereinafter, sometimes referred to as an intermediate transfer belt) as an electrophotographic member will be described below, but the present disclosure is not limited to this embodiment. The electrophotographic image forming apparatus preferably includes the electrophotographic member described above as an intermediate transfer belt. The intermediate transfer belt is a member that secondarily transfers the toner image transferred from the photosensitive drum to a recording material. Note that FIG. 2 is a schematic cross-sectional view showing an example of a full-color electrophotographic apparatus using an electrophotographic process.

[0064] This electrophotographic device has a so-called tandem configuration in which electrophotographic stations of multiple colors are arranged side by side in the rotation direction of an electrophotographic member (intermediate transfer belt). In the following description, the symbols of the components relating to the colors yellow, magenta, cyan, and black are suffixed with Y, M, C, and k, respectively, but the suffixes may be omitted for similar components.

[0065] In FIG. 2, charging devices 2Y, 2M, 2C, 2k, exposure devices 3Y, 3M, 3C, 3k, developing devices 4Y, 4M, 4C, 4k, and an intermediate transfer belt 6 are arranged around photosensitive drums (photoconductors, image carriers) 1Y, 1M, 1C, 1k.

[0066] The photosensitive drum 1 is rotationally driven at a predetermined peripheral speed (process speed) in the direction of the arrow F. The charging device 2 charges the peripheral surface of the photosensitive drum 1 to a predetermined polarity and potential (primary charging). The laser beam scanner as the exposure device 3 outputs laser light that is on / off modulated in response to image information input from an external device such as an image scanner or computer (not shown), and scans and exposes the charged surface of the photosensitive drum 1. This scanning and exposure forms an electrostatic latent image on the surface of the photosensitive drum 1 according to the target image information.

[0067] The developing devices 4Y, 4M, 4C, and 4k contain toner of each color component of yellow (Y), magenta (M), cyan (C), and black (k), respectively. Then, the developing device 4 to be used is selected based on image information, and developer (toner) is developed on the surface of the photosensitive drum 1, and the electrostatic latent image is visualized as a toner image. In this embodiment, a reversal development method is used in which toner is attached to the exposed portion of the electrostatic latent image to develop it. Furthermore, the electrophotographic means is composed of such charging devices, exposure devices, and developing devices.

[0068] The intermediate transfer belt 6 is disposed so that its outer circumferential surface is in contact with the surface of the photosensitive drum 1, and is tensioned by a plurality of tension rollers 20, 21, and 22. The intermediate transfer belt 6 rotates in the direction of the arrow G. In this embodiment, the tension roller 20 is a tension roller that controls the tension of the intermediate transfer belt 6 to be constant, the tension roller 22 is a drive roller for the intermediate transfer belt 6, and the tension roller 21 is an opposing roller for secondary transfer. In addition, primary transfer rollers 5Y, 5M, 5C, and 5k are disposed at primary transfer positions opposing the photosensitive drum 1 with the intermediate transfer belt 6 interposed therebetween.

[0069] The unfixed toner images of each color formed on the photosensitive drum 1 are electrostatically transferred in sequence onto the intermediate transfer belt 6 by applying a primary transfer bias of positive polarity, which is opposite to the charge polarity of the toner, to the primary transfer roller 5 from a constant voltage source or a constant current source. Then, a full-color image is obtained on the intermediate transfer belt 6 in which the unfixed toner images of the four colors are superimposed. 6 rotates while carrying the toner image thus transferred from the photosensitive drum 1. After the primary transfer, the surface of the photosensitive drum 1 is cleaned by a cleaning device 11 (11Y, 11M, 11C, 11k) to remove residual toner from the surface, and the image forming process is repeated.

[0070] At the secondary transfer position of the intermediate transfer belt 6 facing the transport path of the recording material 7, a secondary transfer roller (transfer unit) 9 is disposed in pressure contact with the toner image carrying surface of the intermediate transfer belt 6. At the secondary transfer position, on the back side of the intermediate transfer belt 6, an opposing roller 21 is disposed, which serves as an opposing electrode for the secondary transfer roller 9 and to which a bias is applied. When the toner image on the intermediate transfer belt 6 is transferred to the recording material 7, a bias of the same polarity as the toner is applied to the opposing roller 21 by secondary transfer bias application means 28, and for example, -1000 to -3000 V is applied, causing a current of -10 to -50 μA to flow. The transfer voltage at this time is detected by transfer high voltage detection means 29. Furthermore, downstream of the secondary transfer position, a cleaning device (belt cleaner) 12 is provided to remove toner remaining on the intermediate transfer belt 6 after secondary transfer.

[0071] The recording material 7 introduced from the registration roller pair 8 to the secondary transfer position is sandwiched and transported at the secondary transfer position, and at this time, a constant voltage bias (transfer bias) controlled to a predetermined value is applied from a secondary transfer bias application means 28 to the opposing roller 21 of the secondary transfer roller 9. A transfer bias of the same polarity as the toner is applied to the opposing roller 21, so that the four full-color images (toner images) superimposed on the intermediate transfer belt 6 at the transfer site are transferred collectively to the recording material 7, and a full-color unfixed toner image is formed on the recording material. The recording material 7 to which the toner image has been transferred is transported from the secondary transfer position in the direction of arrow H and introduced into a fixing device (not shown) where it is heated and fixed. EXAMPLES

[0072] EXAMPLES The present disclosure will be specifically described below with reference to examples and comparative examples, but the present disclosure is not limited thereto.

[0073] The measurement and evaluation methods used in each example are described below. In each example, a conductive belt, which is an intermediate transfer belt having an endless shape, was prepared as the electrophotographic member.

[0074] (Measurement of surface resistivity) The surface resistivity of the electrophotographic member was measured in accordance with Japanese Industrial Standards (JIS) K6911:2006. The measuring device used was a high resistance meter (product name: Hiresta UP MCP-HT450, manufactured by Mitsubishi Chemical Analytic Co., Ltd.) with a main electrode having an inner diameter of 50 mm, a guard ring electrode having an inner diameter of 53.2 mm, and a probe having an outer diameter of 57.2 mm (product name: UR-100, manufactured by Mitsubishi Chemical Analytic Co., Ltd.) A voltage of 250 V was applied for 10 seconds to the electrophotographic member to be measured, and the surface resistivity was measured at four points in the circumferential direction of the outer surface of the resin layer of this electrophotographic member.

[0075] (ρs) The electrophotographic member was left for 12 hours in an environmental test room controlled at a temperature of 23° C. and a relative humidity of 50%. Thereafter, in an environment of a temperature of 23° C. and a relative humidity of 50%, the surface resistivity of the electrophotographic belt was measured at four points by the above-mentioned measuring method, and the arithmetic average value of the surface resistivity was taken as ρs (before energization) and was used as an index of electrical resistance.

[0076] The electrophotographic members obtained in the Examples and Comparative Examples were mounted as intermediate transfer belts in a transfer unit of a full-color electrophotographic apparatus (product name: HP Color Laser Jet CP4025dn; manufactured by Hewlett-Packard Co.) having the structure shown in FIG. 2. Then, a solid cyan image was printed on the transfer belt 2000 times in an environment of normal temperature and humidity (temperature 25° C., relative humidity 55%). 00 sheets were printed. Thereafter, the intermediate transfer belt was removed from the electrophotographic apparatus, and ρs was measured in the same manner as above, and this value was taken as ρs (after energization). The value of ((ρs (after current application) - ρs (before current application)) / ρs (before current application) x 100) was defined as the resistance change rate, which was used as an index of the resistance increase fluctuation after continuous current application.

[0077] (Image evaluation) In the image formation using the above electrophotographic device, the 100th sheet of A4-sized paper was printed with a cyan solid image (hereinafter also referred to as the "initial image after energization"), which was visually observed to evaluate the initial image quality after energization. In addition, the final solid cyan image formed on the A4 size paper (hereinafter also referred to as the "final image") was visually observed to evaluate the image quality after energization. The observation results were evaluated according to the following criteria. Rank A: No unevenness is observed at all. Rank B: Minor unevenness is observed in some areas. Rank C: Unevenness is observed in about 20% of the observed image. Rank D: Unevenness is observed over half or more of the observed image. The above evaluation results are shown in Table 5.

[0078] (Materials used to form resin layers in the examples and comparative examples) <Preparation of ionic conductive agent> [Ionic Conductive Agents 1-3] As ion conductive agents 1 to 3, the following commercially available products were prepared. Ionic Conductive Agent 1: 1-Ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (Kanto Chemical Co., Ltd.) Ionic Conductive Agent 2: 1-Butyl-3-methylimidazolium bis(fluorosulfonyl)imide (Kanto Chemical Co., Ltd.) Ionic Conductive Agent 3: 1-Octyl-4-methylpyridinium bisfluorosulfonylimide (product name: Elexcel AS-804; manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)

[0079] Ion conductive agent 4: Ion conductive agent 4 was synthesized according to Production Example 1 below. [Production Example 1: Synthesis of Ion Conductive Agent 4] 50 ml of tetrahydrofuran (THF) (Kanto Chemical Co., Ltd.) was added to a recovery flask equipped with a Dimroth condenser and containing a stirrer, 24.5 g of sodium hydride (Kanto Chemical Co., Ltd.) was dispersed in the THF, and the recovery flask was cooled in an ice bath. Next, a solution of 17.0 g of imidazole (Kanto Chemical Co., Ltd.) as a nucleophile dissolved in 100 ml of THF was dropped into the recovery flask. The ice bath was then removed, and the mixture was stirred at room temperature (23°C) for 2 hours. Next, 121.5 g of 1-bromooctane (Tokyo Chemical Industry Co., Ltd.) was added as an electrophilic agent to the eggplant flask, and the mixture was heated to reflux at 70° C. for 8 hours to react. The reaction solution was filtered, the insoluble matter was washed with THF, and the solvent of the obtained filtrate was distilled off under reduced pressure. The obtained concentrate was dissolved again in dichloromethane and filtered, and the filtrate was recovered, and the dichloromethane was distilled off under reduced pressure. The obtained concentrate was washed with diethyl ether and dried under reduced pressure to obtain a precursor of ion conductive agent 4. Next, the entire amount of the precursor of the ion conductive agent 4 was dissolved in 100 ml of methanol. While stirring the solution, 54.8 g of potassium N,N-bis(fluorosulfonyl)imide (trade name: k-FSI, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) dissolved in 100 ml of pure water was added, and the mixture was stirred at room temperature for 24 hours. After the reaction, the methanol was distilled off under reduced pressure, and the mixture was washed with dichloromethane / water. After separation, the organic layer was collected and washed twice with pure water, the solvent was removed by distillation under reduced pressure, and the mixture was dried to obtain an ion conductive agent 4 as a white powder.

[0080] Ion conductive agent 5: Ion conductive agent 5 was synthesized according to Production Example 2 below. [Production Example 2: Synthesis of Ion Conductive Agent 5] 5.86 g of 12,13-Tetracosanedione (1717CheMall), 0.58 g of paraformaldehyde (Tokyo Chemical Industry Co., Ltd.), and 2.96 g of ammonium acetate (Kanto Chemical Co., Ltd.) were placed in a Dimroth condenser-equipped eggplant flask containing a stirrer, and 45.0 ml of ethanol (Kanto Chemical Co., Ltd.) was added to dissolve them. 1.0 ml of acetic acid (Tokyo Chemical Industry Co., Ltd.) was then added dropwise. The mixture was then stirred at 110°C for 4 hours. Next, a saturated aqueous solution of sodium bicarbonate was added so that the pH of the resulting reaction solution became 13. The pH-adjusted reaction solution was separated into dichloromethane and water, and the organic layer was collected. The collected organic layer was washed twice with pure water, and the solvent was removed by distillation under reduced pressure. The mixture was dried to obtain the nucleophile 4,5-diundecylimidazole as a white powder. Thereafter, an ion conductive agent 5 was obtained in the same manner as in Production Example 1, except that the nucleophile in Production Example 1 was changed to 4,5-diundecylimidazole and the electrophile was changed to iodomethane (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0081] The materials used to form the resin layers in the examples and comparative examples are shown in the following Tables 1 and 2. The specific materials and amounts used in each example and comparative example are shown in Table 3 below. The amounts are in parts by mass unless otherwise specified.

[0082] [Table 1] <Synthesis of matrix resin 3> Polyethylene terephthalate resin (homopolymer, product name: TRN-8550FF; manufactured by Teijin Limited) and polyethylene naphthalate (product name: TN8065S, manufactured by Teijin Limited) were mixed. The resins were mixed in a molar ratio of 94:6, and then melted and kneaded at 300°C to cause ester exchange between the two resins. The reaction was carried out to obtain Matrix Resin 3.

[0083] [Table 2]

[0084] [Table 3]

[0085] Example 1 The materials shown in Table 4 were mixed in the amounts shown in Table 4 using a twin-screw extruder (product name: PCM43 A resin composition was prepared by melting and mixing under the following conditions using a thermoplastic elastomer (manufactured by Ikegai Corporation). Output: 6kg / h Screw speed: 225 rpm Barrel control temperature: 270℃ The resin composition thus obtained was melt-extruded under the following conditions using a single-screw extruder (manufactured by Plastics Engineering Research Institute Co., Ltd.) equipped with a spiral cylindrical die (inner diameter: 195 mm, slit width: 1.1 mm) at the tip to produce a cylindrical film of the following size. The cylindrical film thus obtained was used as the conductive belt of Example 1. Output: 6kg / h Die temperature: 290℃ Size: Outer diameter 201mm, thickness 70μm The evaluation results of this conductive belt are shown in Table 5 below.

[0086] [Examples 2 to 5, 8 to 14] Conductive belts of Examples 2 to 5 and 8 to 14 were obtained in the same manner as in Example 1, except that the blending ratio of the resin composition was changed as shown in the following Table 4. The evaluation results thereof are shown in the following Table 5.

[0087] [Examples 6 and 7, Comparative Example 2] The conductive belts shown in Examples 6 and 7 and Comparative Example 2 were obtained in the same manner as in Example 1, except that the formulation of the resin composition was changed as shown in Table 4 below, and the barrel control temperature was changed to 240° C. and the die temperature was changed to 260° C. The evaluation results are shown in Table 5 below. In addition, even in Example 6 in which modified polyethylene terephthalate was used as the matrix resin, the conductive belt did not break due to a decrease in crystallinity.

[0088] [Comparative Examples 1 and 3] The conductive belts shown in Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the blending of the resin composition was changed as shown in Table 4 below, and the barrel control temperature was changed to 200° C. and the die temperature was changed to 220° C. The evaluation results are shown in Table 5 below.

[0089] Example 15 A resin composition was prepared by hot melt kneading each material according to the composition shown in Table 4 below using a twin-screw extruder (product name: TEX30α, manufactured by Japan Steel Works, Ltd.). The hot melt kneading temperature was adjusted to be within the range of 260°C to 280°C, and the hot melt kneading time was about 3 minutes. The obtained resin composition was pelletized and dried at a temperature of 140°C for 6 hours.

[0090] Next, a preform was produced from the pellets using an injection molding machine (product name: SE180EV-A, manufactured by Sumitomo Heavy Industries, Ltd.) with a cylinder temperature set to 300° C. The injection mold temperature at this time was set to 30° C. The preform was placed in a heating device at a temperature of 500°C to soften it, and then heated to 500°C. The preform was then placed in a primary blow molding machine. Then, in the blow mold, blow molding was performed using the force of a stretch bar and air (blow air injection part) at a preform temperature of 70°C, air pressure of 0.3MPa, and stretch bar speed of 1000mm / s to obtain a blown bottle.

[0091] Next, the obtained blow bottle was set in a secondary blow molding device, and a cylindrical nickel mold was placed so as to surround the outer circumference of the blow bottle. Then, an air pressure of 0.1 MPa was applied to the inside of the blow bottle, and the blow bottle was transferred to the inner surface of the mold while adjusting so that air would not leak to the outside. While rotating the cylindrical mold, the cylindrical mold was heated to 200°C by a heater for a total of 60 minutes. After that, the cylindrical mold was cooled to room temperature of 23° C. with air, and the pressure applied to the inside of the bottle was released to obtain a heated blown bottle.

[0092] Both ends of the blown bottle after heating were cut to obtain a single-layer conductive belt consisting of only a resin layer. The thickness of the obtained conductive belt was 70 μm, and the circumference was 792.0 mm. The evaluation results of this conductive belt are shown in Table 5 below.

[0093] [Table 4] For Others 1 and Others 2, the materials shown in Table 3 were used.

[0094] [Table 5] For example, the entry 6.3E+09 in the table is 6.3 x 10 9 This indicates that.

[0095] The present disclosure relates to the following configurations. (Configuration 1) 1. An electrophotographic member comprising: The electrophotographic member has a resin layer, The resin layer has electrical conductivity, The resin layer is An aromatic ring-containing polyester; a fluorosulfonylimide anion and a cation having a double bond; Including, The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) Modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units is 6 mol % or less of the total acid monomer units, and (iv) Modified polyethylene naphthalate in which the proportion of acid monomer units other than naphthalene acid units is 6 mol % or less of the total acid monomer units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv) above. Electrophotographic member characterized in that: (Configuration 2) 2. The electrophotographic member according to embodiment 1, wherein the cation having a double bond has an aromatic heterocyclic structure. (Configuration 3) The electrophotographic member according to embodiment 1 or 2, wherein the cation having a double bond is at least one cation selected from the group consisting of cations represented by the following formula (2-1) and cations represented by the following formula (2-2): TIFF2025015441000011.tif56153 In the formula, R1, R2, R3, and R4 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. (Configuration 4) When one selected from the group consisting of R1 and R2 is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, The electrophotographic member according to Configuration 3, wherein when one selected from the group consisting of R3 and R4 is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. (Configuration 5) 4. The electrophotographic member according to embodiment 3, wherein R1, R2, R3 and R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms. (Configuration 6) The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, or (iii) Modified polyethylene terephthalate, in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units, and the acid units other than terephthalic acid units are isophthalic acid units. 6. The electrophotographic member according to any one of Configurations 1 to 5, (Configuration 7) 7. The electrophotographic member according to any one of configurations 1 to 6, wherein the aromatic ring-containing polyester is polyethylene naphthalate or polyethylene terephthalate. (Configuration 8) The electrophotographic member according to any one of Configurations 1 to 7, wherein the sum of the contents of the cation having a double bond and the fluorosulfonylimide anion in the resin layer is 0.5 to 10.0% by mass based on the mass of the resin layer. (Configuration 9) The surface resistivity ρs measured on the outer surface of the resin layer at a temperature of 23° C. and a relative humidity of 50% is 1.0×10 6 ~1.0×10 12 9. The electrophotographic member according to any one of configurations 1 to 8, wherein the resistivity is Ω / □. (Configuration 10) 10. The electrophotographic member according to any one of Configurations 1 to 9, wherein the electrophotographic member is an intermediate transfer member. (Configuration 11) The electrophotographic member is an electrophotographic belt having an endless belt shape. 11. The electrophotographic member according to any one of Configurations 1 to 10. (Configuration 12) 12. An electrophotographic image forming apparatus comprising the electrophotographic member according to any one of Configurations 1 to 11 as an intermediate transfer member. (Configuration 13) An aromatic ring-containing polyester; a fluorosulfonylimide anion and a cation having a double bond; Contains The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) Modified polyethylene terephthalate in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units, and (iv) Modified polyethylene naphthalate in which the proportion of acid units other than naphthalene acid units is 6 mol % or less of the total acid units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv).

Claims

1. 1. An electrophotographic member comprising: The electrophotographic member has a resin layer, The resin layer has electrical conductivity, The resin layer is An aromatic ring-containing polyester; a fluorosulfonylimide anion and a cation having a double bond; Including, The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) a modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units is 6 mol % or less of the total acid monomer units; and (iv) Modified polyethylene naphthalate in which the proportion of acid monomer units other than naphthalene acid units is 6 mol % or less of the total acid monomer units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv) above. Electrophotographic member characterized in that:

2. 2. The electrophotographic member of claim 1, wherein said cation having a double bond has an aromatic heterocyclic structure.

3. 2. The electrophotographic member according to claim 1, wherein the cation having a double bond is at least one cation selected from the group consisting of cations represented by the following formula (2-1) and cations represented by the following formula (2-2): In the formula, R 1 , R 2 , R 3 , R 4 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms.

4. The R 1 Or R 2 When one selected from the group consisting of is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, The R 3 Or R 4 4. The electrophotographic member of claim 3, wherein when one selected from the group consisting of: is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms.

5. The R 1 , R 2 , R 3 , R 4 The electrophotographic member of claim 3, wherein each independently is a hydrocarbon group having from 1 to 4 carbon atoms.

6. The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, or (iii) A modified polyethylene terephthalate in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units, and the acid units other than terephthalic acid units are isophthalic acid units.

2. The electrophotographic member of claim 1 wherein:

7. 2. The electrophotographic member of claim 1, wherein said aromatic ring-containing polyester is polyethylene naphthalate or polyethylene terephthalate.

8. 2. The electrophotographic member according to claim 1, wherein the sum of the contents of the cation having a double bond and the fluorosulfonylimide anion in the resin layer is 0.5 to 10.0% by mass based on the mass of the resin layer.

9. The surface resistivity ρs measured on the outer surface of the resin layer at a temperature of 23° C. and a relative humidity of 50% is 1.0×10 6 ~1.0 x 10 12 3. The electrophotographic member of claim 1, wherein the resistivity is Ω / □.

10. 2. The electrophotographic member of claim 1 wherein said electrophotographic member is an intermediate transfer member.

11. The electrophotographic member is an electrophotographic belt having an endless belt shape.

2. The electrophotographic member of claim 1.

12. 12. An electrophotographic image forming apparatus comprising the electrophotographic member according to claim 1 as an intermediate transfer member.

13. An aromatic ring-containing polyester; a fluorosulfonylimide anion and a cation having a double bond; Contains The aromatic ring-containing polyester is (i) polyethylene naphthalate, (ii) polyethylene terephthalate, (iii) a modified polyethylene terephthalate in which the proportion of acid units other than terephthalic acid units is 6 mol % or less of the total acid units; and (iv) Modified polyethylene naphthalate in which the proportion of acid units other than naphthalene acid units is 6 mol % or less of the total acid units. or a mixture of two or more polyesters selected from the group consisting of (i) to (iv).

Citation Information

Patent Citations

  • Conductive belt and electrophotographic device

    JP2014132329A

  • Electrophotographic member, process cartridge, and electrophotographic image forming apparatus

    JP2020024404A